Modelling the species jump: towards assessing the risk of human infection from novel avian influenzas. Issue 9 (September 2015) - Hill, A. A.; Dewé, T.; Kosmider, R.; Von Dobschuetz, S.; Munoz, O.; Hanna, A.; Fusaro, A.; De Nardi, M.; Howard, W.; Stevens, K.; Kelly, L.; Havelaar, A.; et al.
Abstract : The scientific understanding of the driving factors behind zoonotic and pandemic influenzas is hampered by complex interactions between viruses, animal hosts and humans. This complexity makes identifying influenza viruses of high zoonotic or pandemic risk, before they emerge from animal populations, extremely difficult and uncertain. As a first step towards assessing zoonotic risk of influenza, we demonstrate a risk assessment framework to assess the relative likelihood of influenza A viruses, circulating in animal populations, making the species jump into humans. The intention is that such a risk assessment framework could assist decision-makers to compare multiple influenza viruses for zoonotic potential and hence to develop appropriate strain-specific control measures. It also provides a first step towards showing proof of principle for an eventual pandemic risk model. We show that the spatial and temporal epidemiology is as important in assessing the risk of an influenza A species jump as understanding the innate molecular capability of the virus. We also demonstrate data deficiencies that need to be addressed in order to consistently combine both epidemiological and molecular virology data into a risk assessment framework.